Intensitas Penggunaan Smartphone Dalam Dunia Pendidikan Kedinasan Terhadap Perilaku Komunikasi - Aryo Seno, Fiqih Bagus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2020)
Smartphones are the new media in terms of the communication process, one of these types of gadgets has a lot of great benefits in life. It is not only used to communicate with each other, the fact that the smartphone also has a very wide function. Some high schools have a prohibition of Tarunanya restrictions on smartphones, but the Institute of Correctional Sciences which is a high school under the auspices of the Ministry of Justice and Human rights have the rules of using smartphones to communicate in the process of learning, training and parenting. The research uses one independent variable (X) i.e. the intensity of smartphone usage and one dependent variable (Y) i.e. communication behaviour. Primary Data is collected through a survey method of 100 respondents using an insedental sampling approach. Theories used include communication theory, new media theory, communication psychology and dependency theory. The results showed that the intensity of smartphone use has significant effect on communication behavior of 69% and the remaining 31% is influenced by other factors not found in the study.